Determination of the spin Hall angle in single-crystalline Pt films from spin pumping experiments - Sascha Keller; Laura Mihalceanu; Matthias R Schweizer; Philipp Lang; Björn Heinz; Moritz Geilen; Thomas Brächer; Philipp Pirro; Thomas Meyer; Andres Conca; Dimitrios Karfaridis; George Vourlias; et al. (New Journal of Physics, 2018)
We report on the determination of the spin Hall angle in ultra-clean, defect-reduced epitaxial Pt films. By applying vector network analyzer ferromagnetic resonance spectroscopy to a series of single crystalline Fe (12 nm) /Pt ( t _Pt ) bilayers we determine the real part of the spin mixing conductance (4.4 ± 0.2) × 10 ^19 m ^−2 and reveal a very small spin diffusion length in the epitaxial Pt (1.1 ± 0.1) nm film. We investigate the spin pumping and ISHE in a stripe microstucture excited by a microwave coplanar waveguide antenna. By using their different angular dependencies, we distinguish between spin rectification effects and the inverse spin Hall effect. The relatively large value of the spin Hall angle (5.7 ± 1.4)% shows that ultra-clean e-beam evaporated non-magnetic materials can also have a comparable spin-to-charge current conversion efficiency as sputtered high resistivity layers.